Happiness, Work, and Identity - Clemens Hetschko; Andreas Knabe; Ronnie Schöb (Global Labor Organization (GLO), 2021)
This chapter introduces identity utility to the study of (un)employment and (un)happiness. The concept is described in terms of an augmented utility function, the implications of which are assessed in light of the empirical literature on unemployment and well-being. Studies on unemployed persons' affective and cognitive well-being allow assessing the importance of the loss of identity utility relative to other nonmonetary consequences of joblessness, such as fewer social contacts and a lack of a structure in daily life. Unlike life satisfaction, unemployment leaves affective well-being mostly unaffected, which points to a major relevance of the loss of identity. This view is corroborated further by studies on the importance of the social norms to work and be self-reliant for the life satisfaction of the unemployed, as well as by studies showing the positive life satisfaction effect of retirement on unemployed workers. Based on this strong evidence for identity utility losses of unemployed persons, the notion of identity utility is used to explain heterogeneity in the effect of unemployment on life satisfaction. It is also linked to further consequences of unemployment, such as social exclusion and stigmatization. Moreover, this chapter uses identity utility to assess the likely effectiveness of labor market policies in alleviating the misery of the unemployed. Finally, research on work, happiness and identity is reconciled with a more standard economics view on labor supply based on studies examining the impact of working hours on workers' well-being.
Keywords: D91; I31; J26; J60; 330; employment status; identity; subjective well-being; affective and cognitive well-being